hallamlab/BLOB: Blob_MS_figures_v32.1 - STraving; Ryan (Zenodo, 2021)
First release of Blob_MS_figures_v32.Rmd containing the Rmarkdown documentation for all (except network analyses and visualizations) statistical and most of the graphical outputs, done in R and RStudio. Content: Code and data repository for the BLOB manuscript "Prokaryotic responses to a warm temperature anomaly in northeast subarctic Pacific waters". Sachia J. Traving1†, Colleen T. E. Kellogg2, Tetjana Ross3, Ryan McLaughlin4, Brandon Kieft1, Grace Y. Ho1‡, Angelica Pena3, Martin Krzywinski5, Marie Robert3, Steven J. Hallam1,4,6,7,8* Affiliations 1Department of Microbiology & Immunology, University of British Columbia, Vancouver, BC V6T 1Z1, Canada. 2Hakai Institute, BC, Canada. 3Institute of Ocean Sciences, Fisheries and Ocean Canada, BC, Canada. 4Graduate Program in Bioinformatics, University of British Columbia, Vancouver, BC V6T 1Z4, Canada. 5Genome Sciences Centre, BC Cancer Agency, Vancouver, BC, V5Z 4S6, Canada 6Genome Science and Technology Program, University of British Columbia, 2329 West Mall, Vancouver, BC V6T 1Z4, Canada. 7Life Sciences Institute, University of British Columbia, Vancouver, BC V6T 1Z3, Canada. 8ECOSCOPE Training Program, University of British Columbia, Vancouver, BC V6T 1Z3, Canada. †Current address: HADAL and Nordcee, Department of Biology, University of Southern Denmark, Campusvej 55, 5230 Odense M, Denmark ‡Current address: Max Planck Institute for Marine Microbiology, Celsiusstraße 1, 28359 Bremen, Germany